Izbrana bibliografija literarnozgodovinskih monografij, razprav in člankov s področja slovenske izseljenske književnosti - Žitnik Serafin, Janja (Dve domovini, 1993)
The article is a selected bibliography of scientific monographs, treatises, and articles in the field of the history of Slovene emigrant literature. The bibliography comprises domestic and foreign publications on the subject.
Keywords: bibliografije; bibliographies; emigrant literature; emigration; izseljenska književnost; izseljenstvo; literarna zgodovina; literary history; Slovene emigrants; slovenski izseljenci